PROSTHETIC STOMATITIS: DEVELOPMENT, DIAGNOSIS, TREATMENT AND PREVENTION - A LITERATURE REVIEW - Thaís Duarte Brasileiro, Camilla; Maria do Vale Veras Marques, Fabianne; da Silva Sena, Cristiano; de Souza Pereira, Malvina; Ferreira Pedrosa, Ricardo; Elizabete Pereira de Lima, Claudia; Ferraz Goiana Leal, André (Health and Society, 2022)
Introduction: Candidiasis or Candidosis are designated names designated as infectious names for fungi of the genus Candida spp., which establish a commensal relationship with the immune system when the system is depressed or by some pathogenic infections. As proposals of oral candidiasis can be hyperplastic in primary and secondary cited by the following types: pseudoplastic, erythematous, pseudomembrane, erythematous; there is a category called “lesions also associated with Candida spp.”, which includes denture stomatitis (PE). Knowing the relationship between the development of the disease and the use of dental prosthesis, the present work aims to carry out a literature review on the subject. Methodology: This is a descriptive work with a qualitative aspect of literature review, where they were used as sources of scientific and scientific research. The search platforms used were PubMed, Scielo and the Virtual Health Library. Results and discussion: The presence of devices or devices such as appliances or orthodontic appliances can provoke or modify the best of the microbiota, due to the physical-bio oral environment. In addition, the prosthesis is often related to the use of oral prostheses, such as traumatic ulcers, mucogingival hyperplasia and many oral candidiasis. One of the causes of PE is the proper use of the prosthesis, which, associated with poor hygiene, can be a factor that potentiates the disease; therefore, it is extremely important that the patient is advised about the risk of developing the condition and how to avoid it. Final considerations: The relationship between the use of dental prosthesis and the development of oral candidiasis is well related in the literature. Therefore, dental professionals must take care of patients who use the device for disease care, seeking to improve the possibility of disease development.